Percepção ambiental de grupos representativos da comunidade de Itaoca, São Gonçalo-RJ - Couto, Márcia Nazareth Cordovil do (2009)
This work approaches human beings and nature relationships through environmental perception. Such perception allows relating importance, valorization and interaction between individuals and its environment. Assuming that the form in which individual interacts with its environment corresponds to its personal representations, the study of the environmental perception can be used to identify problems of a community. Besides this it is an important instrument in supplying information to support environmental methodologies and proposes that involve the community in management implementation processes. This research was accomplished with fishermen, crab catchers, crab scrawniers and food/drink standers. These groups are of expressive representativeness in the Itaoca community, in the District of São Gonçalo, RJ. Mangroves and rivers in the area contribute to the Guanabara Bay and are pressured by intense degradation process. The environmental perception of those groups and their links to the current local environmental situation are aims of this research. The study area was characterized through secondary data and photographic registration. Environmental perception was accomplished by semi-structured interview. The findings allow characterizing Itaoca resident s environmental perception, and give the main aspects that should be taken into account in developing projects that include human communities.